Analisa Kebijakan Pemerintah Terkait Ancaman Pengangguran Pasca Kenaikan Inflasi - Delvian Yosuky; Felix Santono; Felycia, Felycia; Tio Sania (Universitas Maritim AMNI Semarang, 2022)
The events of the covid-19 pandemic produce an uncertain future. This has a very far-reaching influence on capitalization of capitalization and also social problems such as increasing levels of violence and crime rates. The purpose of this study is to analyze government policies regarding reactions due to inflation, especially in Indonesia. Inflation rate has a negative effect on the reaction load. The inflation rate affects the response because when the stimulus increases, inflation will decrease and vice versa. There are several government policies in overcoming pressure due to inflation, namely creating jobs, changing the investment climate, spreading several economic stimulus, and improving the quality of human resources through education.